2021
DOI: 10.1016/j.aca.2020.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and challenges associated with the determination of new psychoactive substances in urine and wastewater – A tutorial

Abstract: New psychoactive substances (NPS), often designed as (legal) substitutes to conventional illicit drugs, are constantly emerging in the drug market and being commercialized in different ways and forms. Their use continues to cause public health problems and is therefore of major concern in many countries. Monitoring NPS use, however, is arduous and different sources of information are required to get more insight of the prevalence and diffusion of NPS use. The determination of NPS in pooled urine and wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 129 publications
0
26
0
Order By: Relevance
“…For example, a study reported the concentration of 1.3 ng ml −1 of carfentanil in urine (Müller et al ., 2018). Moreover, it is expected that the urine samples will be highly diluted in wastewater (Bijlsma et al ., 2021), which can also further hamper the detection. Therefore, assuming carfentanil is eliminated into urine (or faeces) at very low levels, the potential in‐sewer biotransformation of carfentanil through microbial hydrolysis might contribute to its complete or partial degradation in wastewater, and potentially to the formation of an exclusively microbial product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study reported the concentration of 1.3 ng ml −1 of carfentanil in urine (Müller et al ., 2018). Moreover, it is expected that the urine samples will be highly diluted in wastewater (Bijlsma et al ., 2021), which can also further hamper the detection. Therefore, assuming carfentanil is eliminated into urine (or faeces) at very low levels, the potential in‐sewer biotransformation of carfentanil through microbial hydrolysis might contribute to its complete or partial degradation in wastewater, and potentially to the formation of an exclusively microbial product.…”
Section: Resultsmentioning
confidence: 99%
“…Wastewater‐based epidemiology (WBE) is an innovative approach that has been successfully applied to monitoring ‘traditional’ illicit drugs and novel psychoactive substances (NPSs) in wastewater to estimate drug consumption by a given population (van Nuijs et al ., 2011; Castiglioni et al ., 2014; Emke et al ., 2018; Bijlsma et al ., 2021; de Campos et al ., 2021). The premise of this approach is that any substance consumed by individuals is excreted in the parent or metabolite forms through urine and faeces and reaches the sewage and the wastewater treatment plant (WWTP) (Castiglioni et al ., 2014; Bishop et al ., 2020; de Campos et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to keep up with the rapid proliferation of NPS the WWA field has seen a significant increase in qualitative screening approaches made possible through the use of high resolution mass spectrometry (HRMS) (Quadrupole-TOF or Orbitrap systems). Such HRMS instruments capture a wide m/z value range at a good sensitivity without a predetermined target list (Bijlsma et al 2020a). The value of this technology is the ability to provide wide-scope screening methods for NPS in wastewater, showing us how many and which compounds are present.…”
Section: -Qualitative and Quantitative Mass Spectrometric Analysismentioning
confidence: 99%
“…The most common transport conditions are: package carefully, and then transport on ice to freeze fully (-18/20 degrees celsius) at the laboratory until analysis (Carlson et al 2013;Yargeau et al 2014; see Table 1). There is a lack of biotransformation and metabolism studies for many NPS, meaning their stability is largely unknown, so keeping the compounds as preserved as possible is important in case of low stability (Couto et al 2018;Bijlsma et al 2020a;Bijlsma et al 2020b).…”
mentioning
confidence: 99%
“…Moreover, IM-MS solved the problem that MS was limited for distinguishing isomeric species. The ion's mass-to-charge ratio (m/z) and average collision cross-section (CCS) can be obtained, which leads to the rising popularity in many fields, including natural products [43,44], microorganisms [45], carbohydrates [46,47], lipidomics [48][49][50], proteomics [51,52], food [53], and environmental samples [54,55]. With current advances in apparatus, IMS is used as a tool in analytical and bioanalytical applications, rather than as a detector for chemical warfare agents and explosives.…”
Section: Introductionmentioning
confidence: 99%